Resisting Call Centre Work: The Aliant Strike and Convergent Unionism in Canada. (1st July 2009) - Enda Brophy,
Abstract : Countering the more placid depictions of call-centre work on offer from academic literature, this paper illuminates the labour antagonisms currently being produced within this growing form of employment. It brings into sharper focus one of the ways in which call centre workers are organising to protect and their interests, by describing their participation in the emerging model of 'convergent' trade unionism of the Communications, Energy, and Paperworkers Union of Canada (CEP) and their 2004 strike against the Canadian telecommunications company Aliant. The five-month strike was provoked by a set of processes that characterised the transformation of the Canadian telecommunications sector in the 1990s, including the privatisation of public telephone companies, corporate convergence, and the restructuring of the labour process at the telecommunications companies that emerged. Drawing on the descriptions offered by a group of call-centre workers who are members of Local 506 of the CEP, the paper focuses on the transformation of the Aliant customer contact labour process from its 'help-desk' functions towards conditions prevailing within non-unionised outsourced call centres across New Brunswick, and recounts the 2004 strike. It concludes by assessing the significance of these events for unionised call-centre workers in the Canadian telecommunications sector and reflecting on how convergent unionism might be extended to include non-unionised workers at outsourced call centres across the region.